CyberKnife Stereotactic Radiosurgery System for Pituitary Tumors and Pulmonary Cancer Bone Metastases: Initiating a New Chapter in Stereotactic Radiotherapy - CHENG Weishi; LIAN Xin; PANG Tingtian; ZHANG Yue; SUN Yuliang; LIU Zhikai (Xiehe Yixue Zazhi)
The CyberKnife, an acronym for the stereotactic radiosurgery platform, represents an image-guided stereotactic radiotherapy technique. This technology precisely delivers ionizing radiation to tissues, effectively damaging tumor cells, and is suitable for radiotherapy of both intracranial and extracranial tumors. This article reports the first performance of CyberKnife by radiotherapy at Peking Union Medical College Hospital, including a patient with uncontrolled pituitary adenoma after surgery and radiotherapy, and another patient with vertebral metastasis following targeted therapy for lung adenocarcinoma. The application of CyberKnife technology in radiotherapy has achieved highly accurate dose delivery, enabling targeted irradiation of tumor lesions while minimizing damage to surrounding normal tissues, thereby yielding relatively ideal clinical outcomes.